2017
DOI: 10.1088/1742-6596/943/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of manipulative in mathematics laboratory

Abstract: Abstract.A manipulative is a teaching aid designed such that students could understand mathematical concepts by manipulating it. This article aims to provide an insight to the characteristics of manipulatives produced in the mathematics laboratory of Universitas Ahmad Dahlan, Indonesia. A case study was conducted to observe the existing manipulatives produced during the latest three years and classified the manipulatives based on the characteristics found. There are four kinds of manipulatives: constructivism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Although instructional strategies like teacher exposition have a place in mathematics education, they are more likely to induce concept memorization than meaningmaking (Senel Tekin et al, 2020). However, it has been strongly suggested that it is possible to make the teaching-learning process of solid geometry meaningful and practical by using different models, one of which is the use of manipulatives (Nduka & Ajoke, 2016), and that teaching mathematics with models as instructional materials improves students' performance (Istiandaru et al, 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Although instructional strategies like teacher exposition have a place in mathematics education, they are more likely to induce concept memorization than meaningmaking (Senel Tekin et al, 2020). However, it has been strongly suggested that it is possible to make the teaching-learning process of solid geometry meaningful and practical by using different models, one of which is the use of manipulatives (Nduka & Ajoke, 2016), and that teaching mathematics with models as instructional materials improves students' performance (Istiandaru et al, 2017).…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Manipulative objects by type consist of concrete objects and virtual objects. Based on its characteristics, it consists of constructivist manipulatives, informative teaching aids and mathematical games (Istiandaru et al, 2017). Mathematical manipulative objects are objects that can be held by individuals where mathematical thinking is conscious and will not be developed (Swan & Marshall, 2010).…”
Section: Introductionmentioning
confidence: 99%